Clinic, etiology and pathogenesis of comorbid conditions in children with hyperkinetic disorder - R. F. Gasanov; I. V. Makarov; D. A. Emelina; E. S. Prokhorenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2024)
Hyperkinetic disorder (HD) refers to chronic non-processual diseases, including among the main symptoms impaired attention, impulsivity and hyperactivity, and corresponds to a mixed version of attention deficit hyperactivity disorder (ADHD).Currently, the etiology of HD is considered as a polyetiological concept, since the formation of any chronic disorder involves, first of all, biological factors, including hereditary mechanisms, nonspecific “trigger” factors and factors of early brain damage that “support” the course of the diseaseand ensuring the uniqueness of each clinical case.The cause of HD is a genetically determined pathogenetic mechanism realized by the dysfunction of monoamine systems, in most cases complicated by minimal residual organic lesions of the central nervous system. In this case, a close connection is established between the clinical manifestations of the disorder in question and the biochemical imbalance of monoamine systems, creating a picture of the clinical and biochemical heterogeneity of the main symptoms of a hyperkinetic disorder. Hyperkinetic disorder is characterized by both clinical and biochemical heterogeneity and is determined by a number of etiological factors that create a variety of manifestations not only of the disease itself, but also of its comorbid conditions, which largely determines the direction of rehabilitation measures. Under these conditions, the specific weight of each factor at different stages of the disease depends on a number of exogenous situations.It is logical in this light, according to the current prevailing view, that GH symptoms are viewed as multidimensional traits due to the concerted action of many common and rare genetic variants in interaction with multiple environmental factors.